Edge-effects dominate copying thermodynamics for finite-length molecular oligomers - Poulton,JM; Ouldridge,TE (New Journal of Physics, 2021)
A signature feature of living systems is their ability to produce copies ofinformation-carrying molecular templates such as DNA. These copies are madeby assembling a set of monomer molecules into a linear macromolecule with a sequence determined by the template. The copies produced have a finite length –they are often “oligomers”, or short polymers – and must eventually detach fromtheir template. We explore the role of the resultant initiation and termination ofthe copy process in the thermodynamics of copying. By splitting the free-energychange of copy formation into informational and chemical terms, we show that,surprisingly, copy accuracy plays no direct role in the overall thermodynamics. Instead, finite-length templates function as highly-selective engines that interconvertchemical and information-based free energy stored in the environment; it is thermodynamically costly to produce outputs that are more similar to the oligomersin the environment than sequences obtained by randomly sampling monomers. Incontrast to previous work that neglects separation, any excess free energy stored incorrelations between copy and template sequences is lost when the copy fully detaches and mixes with the environment; these correlations therefore do not featurein the overall thermodynamics. Previously-derived constraints on copy accuracytherefore only manifest as kinetic barriers experienced while the copy is templateattached; these barriers are easily surmounted by shorter oligomers.